2021
DOI: 10.1021/acs.inorgchem.1c01064
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of ZnIn2S4 on MOF-Derived Ni–Fe LDH to Construct Ternary-Shelled Nanotubes for Efficient Photocatalytic Hydrogen Evolution

Abstract: A rational design of a novel ternary-shelled nanotube is attractive in photocatalytic water splitting. Herein, ZnIn 2 S 4 nanosheets were in situ grown on the surface of MIL-88A-derived Ni−Fe layered double hydroxide (LDH) to fabricate ternary-shelled nanotubes (ZIS@ Ni−Fe LDH) via a self-assembly strategy. Characterization indicates that the ZIS@Ni−Fe LDH heterostructure exhibits a high surface area and a well-defined ternary-shelled hollow structure. The optimal heterostructure presents a remarkably improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…[196] It was found that the 150%-ZIS/10%-MoS 2 /CdS (150 wt% ZIS and 10 wt% MoS 2 ) nanocomposite achieved 7570.4 μmol g À1 h À1 hydrogen production rate, which was about 39.8-fold and 69.0-fold that of pure ZnIn 2 S 4 and CdS, respectively. Meanwhile, AQE reached 30.38% at 420 nm within 6 h. This is concordant with other related investigations of ZnIn 2 S 4 @SiO 2 @TiO 2 , [197] ZnIn 2 S 4 / In(OH) 3 -NiS, [71] ZnIn 2 S 4 @Ni-Fe [198] systems for boosted HER. These works highlighted that the ternary hybrid would be the appealing direction for fabricating highly efficient H 2 -evolution photocatalysts.…”
Section: Photocatalytic Water Splittingsupporting
confidence: 92%
“…[196] It was found that the 150%-ZIS/10%-MoS 2 /CdS (150 wt% ZIS and 10 wt% MoS 2 ) nanocomposite achieved 7570.4 μmol g À1 h À1 hydrogen production rate, which was about 39.8-fold and 69.0-fold that of pure ZnIn 2 S 4 and CdS, respectively. Meanwhile, AQE reached 30.38% at 420 nm within 6 h. This is concordant with other related investigations of ZnIn 2 S 4 @SiO 2 @TiO 2 , [197] ZnIn 2 S 4 / In(OH) 3 -NiS, [71] ZnIn 2 S 4 @Ni-Fe [198] systems for boosted HER. These works highlighted that the ternary hybrid would be the appealing direction for fabricating highly efficient H 2 -evolution photocatalysts.…”
Section: Photocatalytic Water Splittingsupporting
confidence: 92%
“…Because hydrogen is a clean source of energy, photocatalytic water reduction into H 2 has been a potential way to address the energy shortage arising from the overuse of fossil fuels and the serious environmental pollution problems. Generally, light absorption ability, band structures, and the amounts of active sites of the photocatalysts could determine the photocatalytic performance during the hydrogen generation process. Semiconductors (such as CdS, PbS, ZnIn 2 S 4 , etc.) have been applied in the field of photocatalysis on energy and the environment, profiting from their unique electronic structures and optical properties. Among these semiconductors, ZnIn 2 S 4 has a suitable band gap (2.06–2.85 eV) featuring proper band positions for hydrogen evolution reaction (HER) . In addition, benefiting from outstanding photostability and being environmentally friendly compared with CdS and PbS, ZnIn 2 S 4 has been considered to be a promising and efficient HER photocatalyst. However, ZnIn 2 S 4 suffers from serious electron–hole pair recombination and thus possesses poor photocatalytic activity. , To overcome these drawbacks, various solutions such as heterojunction construction, co-catalyst introduction, structure, and morphology control have been employed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the following equation E NHE = E Ag/AgCl + 0.197, E FB of TiO 2 is converted to be −0.19 V versus NHE and E FB of Co 3 O 4 is 1.02 V versus NHE. In general, E CB of n-type semiconductors is 0.10 V negative than E FB , while E VB of p-type semiconductors is 0.10 V positive than E FB . , Thus, E CB of TiO 2 is reckoned at −0.29 V versus NHE, and E VB of Co 3 O 4 is about 1.12 V versus NHE. Furthermore, together with E g values of Co 3 O 4 (1.87 eV) and TiO 2 (2.85 eV) obtained from Tauc plots, the E VB value of TiO 2 and the E CB value of Co 3 O 4 are 2.56 and −0.75 V versus NHE, respectively, according to the equation E CB = E VB – E g …”
Section: Results and Discussionmentioning
confidence: 94%